Analisis Putusan Hakim Terhadap Tindak Pidana Kekerasan Dalam Rumah Tangga (Studi Kasus Putusan Nomor 1189/Pid.Sus/2024/PN Mdn) - Sitompul, Kristina Pujasari; Simbolon, Nur Anisa; Sembiring, Julianti; Panjaitan, Novia; Siahaan, Parlaungan Gabriel (Jurnal Media Informatika, 2024)
The case of domestic violence has been tried at the Medan District Court with the issuance of decision No.1189/Pid.Sus/2024/PN MDN. Through this decision, the author intends to conduct research by legally analyzing cases of domestic violence that are in conflict with the law, for criminal acts of domestic violence where women are victims. Based on the basic problems that have been described, the author raises a study entitled "Analysis of Judge's Decisions on Criminal Acts of Domestic Violence. The research method used in this paper is normative juridical, which means focusing only on existing legal regulations. Regardless of the social conditions outside it, normative law is a method that digs deeper into the applicable legal system without considering external factors such as social and economic conditions. Law cannot be separated from the context of society, therefore in making decisions the judge must consider the sense of justice of the community. The court sentenced Daniel guilty, with a prison sentence of 1 year and 6 months. The panel of judges considered Romian's injuries as an aggravating circumstance, while Daniel's polite attitude in court and his regret for his actions were mitigating circumstances. The evidence in the form of a machete was confiscated to be destroyed, and Daniel was charged with court costs of Rp. 5,000.00. Therefore, there needs to be a joint effort to create a safe and supportive environment for everyone without violence. Keywords: KDRT, Decision, Judge,